Correction: Effect of lycium barbarum polysaccharide on ameliorating high-fat diet-damaged spermatogenesis via PCSK9 and TLR4 signaling pathways in obese mice - Jinyuan Wang; Yuru Chen; Rongqian Ni; Mingxuan Su; Yichang Cao; Runtang Zhou; Xiang Li; Jiangming Li; Yuxia Tang; Jiayi Tang; Simin Wang; Linyue Tang; et al. (Molecular Biology Reports, 2026)

WD repeat-containing protein 41 (WDR41) is involved in fertilization and interacts with IZUMO1 and JUNO - Wenjun Zhang; Yangyang Sun; Xu Li; Simin Liu; Huimin Su; Wanjin Xing (Theriogenology, 2026)

A carrier-free hydrogel deriving from bioactive herbal polysaccharide and Cu2+ for healing MRSA-infected diabetic wound by coupling with self-regulated cascade enzyme-mimicking catalytic and photothermal therapy - Siqi Su; Simin Wei; Yingdong Zhou; Yuhui Wang; Yinghui Wang (Chemical Engineering Journal, 2026)

Convallatoxin ameliorates fibroblast-like synoviocytes-mediated synovial inflammation and joint destruction in rheumatoid arthritis by targeting IDH1 - Suling Liu; Huijuan Hu; Yu Kuang; Simin Chen; Kai Sun; Chenxi Peng; Ruiru Li; Fan Su; Liuqin Liang; Qian Qiu; Youjun Xiao; Hanshi Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Effect of lycium barbarum polysaccharide on ameliorating high-fat diet-damaged spermatogenesis via PCSK9 and TLR4 signaling pathways in obese mice - Jinyuan Wang; Yuru Chen; Rongqian Ni; Mingxuan Su; Yichang Cao; Runtang Zhou; Xiang Li; Jiangming Li; Yuxia Tang; Jiayi Tang; Simin Wang; Linyue Tang; et al. (Molecular Biology Reports, 2025)

Comparison of Mineral Levels in Blood and Hair Samples of Healthy Adults: Evaluating the Clinical Utility of Hair Mineral Analysis - Alex Shahverdian; Simin Torabzadeh; David Watts; Steffen Porwollik; Monica Padilla; Jeong Su Lee; Gabriella Perez; Mahtab Jafari (Biological Trace Element Research, 2025)
Minerals play vital roles in human physiology and immunity. Their tightly regulated levels in the human body can be easily measured in blood, but that only provides a snapshot of the mineral status at the time of collection. In contrast, human hair accumulates minerals over time and is less invasive to collect and store. This pilot study compared mineral levels in blood and scalp hair of generally healthy adults to determine whether hair can accurately detect clinically relevant mineral imbalances and evaluate whether a relationship exists between blood and hair measurements. Minerals tested included calcium, magnesium, sodium, potassium, copper, zinc, phosphorus, iron, and selenium. Correlation, linear regression, and agreement analyses were performed before and after statistical outlier removal. A total of 30 subjects (mean age: 69.8 years) participated in the study. Most minerals displayed no significant correlation between hair and blood values. However, a weak but significant inverse correlation between blood and hair was identified for phosphorus ( p = 0.044 in correlation and linear regression analyses). Linear regression analysis before outlier removal also suggested a significant direct correlation of blood and hair values for zinc ( p = 0.0315), but not after outlier removal ( p = 0.2682). Agreement between mineral status in blood and hair (low, normal, high, based on established reference ranges) was non-significant for all minerals tested. In conclusion, a significant relationship between blood and hair mineral concentrations was not established. However, the distinct hair mineral analysis results suggest a unique clinical utility for long-term trends and imbalances.

Acid-resistant iron sludge-based fly ash geopolymer foam for efficient arsenic removal with pH self-regulation - Huiping Zeng; Jiongru Liang; Simin Li; Su Han; Zhanguo Li; Jie Zhang; Dong Li (Environmental Research, 2025)

Mendelian randomization analysis reveals causal associations between autoimmune diseases and female infertility risk - Jinyuan Wang; Haojun Long; Mingxuan Su; Yichang Cao; Runtang Zhou; Xiang Li; Jiangming Li; Yuxia Tang; Jiayi Tang; Simin Wang; Linyue Tang; Ruxin Chen; et al. (Reproductive Toxicology, 2025)

Temporin-GHaR Peptide Alleviates LPS-Induced Cognitive Impairment and Microglial Activation by Modulating Endoplasmic Reticulum Stress - Da-Qi Zhang; Xiaoqian Dong; Simin Su; Linlin Zhang; Jiayu Zhang; Wenjing Yang; Wenting Hu; Lushuang Li; Yanting Song; Xi Xie; Qifu Li; Rong Wang; et al. (Probiotics and Antimicrobial Proteins, 2025)

A carrier-free hydrogel loading silver nanoparticles with photothermal effect to heal refractory diabetic wound by robust bacteria elimination and repair-promotion - Mengke Hao; Yinghui Wang; Yuhui Wang; Siqi Su; Yingdong Zhou; Simin Wei (Chemical Engineering Journal, 2025)

Insight into aroma dynamic changes during the whole manufacturing process of smoked Lapsang Souchong tea - Weiying Su; Zhibin Liu; Simin Huang; Daoliang Wang; Xiaoxiao Feng; Yuan Liu; Li Ni (Food Chemistry, 2025)

Versatile benzthienocarbazole isomer derivatives as efficient TADF emitters and hosts for blue multi-resonance TADF emitters - Deli Li; Jiaji Yang; Simin Jiang; Haoxiang Yuan; Denghui Liu; Zhihai Yang; Guo-Xi Yang; Mengke Li; Xuchuan Jiang; Wei Li; Shi-Jian Su (Chemical Engineering Journal, 2025)

Using a rough-fuzzy DANP technique for analysis of the key factors affecting the development of a green business in the machinery manufacturing sector - Qigan Shao; Huai-Wei Lo; Simin Liu; Changchang Jiang; Peiyao Su (Journal of Cleaner Production, 2024)

Comparison of transit time models for exploring seasonal variation of preferential flow in a Moso bamboo watershed - Jianfeng Gou; Simin Qu; Peng Shi; Huade Guan; Hai Yang; Zhicai Zhang; Jintao Liu; Zhiguo Su (Journal of Hydrology, 2023)

Mineralogical characteristics of root iron plaque and its functional mechanism for regulating Cr phytoextraction of hyperaccumulator Leersia hexandra Swartz - Xuehong Zhang; Chang Su; Yuanyuan Zhang; Simin Lai; Shuo Han; Xingran Zhang; Junjian Zheng (Environmental Research, 2023)

Seasonal variation of transit time distribution and associated hydrological processes in a Moso bamboo watershed under the East Asian monsoon climate - Jianfeng Gou; Simin Qu; Huade Guan; Peng Shi; Zhicai Zhang; Hai Yang; Jintao Liu; Zhiguo Su; Xiaole Han (Journal of Hydrology, 2023)

Spiral donor-based host materials for highly efficient blue thermally activated delayed fluorescence OLEDs - Deli Li; Mengke Li; Wei Li; Wenqi Li; Zijian Chen; Xiaomei Peng; Denghui Liu; Guo-Xi Yang; Simin Jiang; Yiyang Gan; Zhihai Yang; Kunkun Liu; et al. (Chemical Engineering Journal, 2023)

Planar D-σ-A type thermally activated delayed fluorescence material with Intra- and intermolecular charge transfer characteristics - Simin Jiang; Jianyin Lin; Deli Li; Mengke Li; Yanmei He; Wentao Xie; Jiting Chen; Yiyang Gan; Guo-Xi Yang; Zhihai Yang; Wei Li; Shi-Jian Su (Chemical Engineering Journal, 2023)